Proteomics research and related functional classification of liquid sclerotial exudates of Sclerotinia ginseng - Dan Wang; Jun Fan Fu; Ru Jun Zhou; Zi Bo Li; Yu Jiao Xie (PeerJ, 2017)
Sclerotinia ginseng is a necrotrophic soil pathogen that mainly infects the root and basal stem of ginseng, causing serious commercial losses. Sclerotia, which are important in the fungal life cycle, are hard, asexual, resting structures that can survive in soil for several years. Generally, sclerotium development is accompanied by the exudation of droplets. Here, the yellowish droplets of S. ginseng were first examined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and the proteome was identified by a combination of different analytical platforms. A total of 59 proteins were identified and classified into six categories: carbohydrate metabolism (39%), oxidation-reduction process (12%), transport and catabolism (5%), amino acid metabolism (3%), other functions (18%), and unknown protein (23%), which exhibited considerable differences in protein composition compared with droplets of S. sclerotium. In the carbohydrate metabolism group, several proteins were associated with sclerotium development, particularly fungal cell wall formation. The pathogenicity and virulence of the identified proteins are also discussed in this report. The findings of this study may improve our understanding of the function of exudate droplets as well as the life cycle and pathogenesis of S. ginseng.